Energy Aware Heuristic approach for Cluster Head Selection in Wireless Sensor Networks - A. Tamizharasi M. E.; J. Jasmine Selvathai M. E.; A. Kavi Priya; Maarlin R.; Harinetha M. (Institute of Advanced Engineering and Science, 2017)
Wireless sensor networks idea is envisioned and defined as self-deployed, error prone, long living inexpensive communication devices that are densely deployed to collect data from physical space. Sensor nodes communicate with each other to detect events depending on the application, to collect and process data, and to transmit the sensed information to the base station by hopping the data from node to node. Major challenge in wireless network is energy consumption, since the sensor devices are deployed on unattended wide areas and replacing their batteries is not very feasible. Therefore, designing energy-aware algorithms becomes a major challenge for extending the lifetime of sensors. The lifetime of the network can be maximized by selecting the most optimal cluster head. In this paper, a heuristic decision making approach is proposed for producing energy-aware clusters with optimal selection of cluster head. This helps to improve the efficiency and accuracy and overcome the drawbacks like getting trapped at a local extreme in the optimization process.